Non-Contrast Head CT Technique in Severe Head Injury with Suspected Skull Base Fracture at RS Syarif Hidayatullah - Zilatul Azmi Arifin; Nursama Heru Apriantoro; Khairil Anwar (Jurnal Teknologi Kesehatan (Journal of Health Technology), 2025)
Severe head injury (SHI) is a medical emergency that requires fast and accurate imaging evaluation. One of the main challenges in SHI cases is detecting skull base fractures that are not visible through clinical examination. Non-contrast head CT is widely used because it provides detailed visualization of brain and skull structures without the need for contrast agents.This study aims to describe the technical procedure of non-contrast head CT in a patient with clinical signs of SHI and suspected skull base fracture at the Radiology Department of RS Syarif Hidayatullah. The method used was descriptive qualitative with a case study approach. Data were collected through participatory observation and analyzed descriptively.The scan revealed subacute subdural hemorrhage, bilateral subarachnoid hemorrhage, midline shift, right cerebral edema, and signs of herniation. No calvarial fracture was found, but the radiological findings indicated severe brain injury. The scan was performed using 0.48 mm thin slices with proper patient positioning, resulting in optimal image quality.In conclusion, non-contrast head CT is an effective diagnostic tool for identifying structural brain injuries in SHI patients. It is fast, safe, and provides accurate results to support clinical decision-making